Long-Term Surgical Outcome of Trabeculectomy with Mitomycin C: A Comparison Between Primary and Secondary Glaucoma in Thailand - Arampinyokul P; Rojananuangnit K (Clinical Ophthalmology)
Ployroung Arampinyokul,1,2,* Kulawan Rojananuangnit1,* 1Department of Ophthalmology, Mettapracharak (Wat Rai Khing) Hospital, Nakhon Pathom, Thailand; 2Mahidol Bumrungrak Nakhonsawan Medical Center, Nakhon Sawan, Thailand*These authors contributed equally to this workCorrespondence: Kulawan Rojananuangnit, Department of Ophthalmology, Mettapracharak (Wat Rai Khing) Hospital, 52 Moo 2 Rai Khing Sam Pran, Nakhon Pathom, 73210, Thailand, Email Kulawan@me.comPurpose: This study aimed to evaluate the long-term surgical outcomes of trabeculectomy with mitomycin C (MMC) and identify factors associated with surgical failure in Thai patients with primary and secondary glaucoma.Methods: This retrospective study included 421 eyes from 397 patients with glaucoma who underwent trabeculectomy with MMC from January 1, 2012, to December 31, 2015. The patients’ demographics, baseline characteristics, ocular parameters, and postoperative outcomes were analyzed. Surgical success was classified into complete success (IOP = 4– 21 mmHg without anti-glaucoma medication), qualified success (IOP = 4– 21 mmHg with medication), and failure (IOP > 21 mmHg or < 4 mmHg). Factors associated with surgical failure were assessed using Cox regression analysis.Results: The cumulative probability of complete or qualified success at 8 years was 65.9% (95% CI: 59.9%, 71.9%); however, a significantly higher success rate was observed in the primary glaucoma group (75.1%) than in the secondary glaucoma group (47.4%) (p < 0.001). The secondary glaucoma group, particularly those with secondary closed-angle glaucoma, had the lowest success rates. Preoperative IOP, number of anti-glaucoma medications, and visual acuity were significantly different between the two groups. Etiologic factors associated with surgical failure included pseudo-exfoliation glaucoma (adjusted HR 3.23), neovascular glaucoma (adjusted HR 2.87), and secondary angle closure glaucoma (adjusted HR 2.62). Late complications were more prevalent in patients with secondary glaucoma than in those with primary glaucoma and included decreased visual acuity (5.43% vs 10.29%), hypotony (0.26% vs 1.14%), corneal decompensation (1.82% vs 3.40%), and bleb-related infection (0.19%).Conclusion: Trabeculectomy with MMC remains an effective surgical option for primary glaucoma, demonstrating better long-term outcomes compared to its outcomes in patients with secondary glaucoma. Risk factors for surgical failure include specific glaucoma etiologies. These findings would personalize management strategies to optimize surgical approaches based on predictive factors for surgical success.Plain language summary: The study looked at how well a type of eye surgery called trabeculectomy works for people with glaucoma, a condition that causes high pressure in the eye. We reported how successful the surgery was over 8 years and what might make it more likely to fail.The study found that trabeculectomy surgery works better for people with primary glaucoma than for those with secondary glaucoma (glaucoma caused by other health issues). After 8 years, about 75% of primary glaucoma patients had successful results, while only 47% of secondary glaucoma patients did. Secondary glaucoma patients also had more postsurgery problems, like vision loss and infections. These findings would help doctors tailor treatment plans and choose the best surgical approach based on factors that predict surgery success.Keywords: close-angle glaucoma, neovascular glaucoma, open-angle glaucoma, postintraocular surgery glaucoma, pseudoexfoliation glaucoma, uveitic glaucoma